Percepción de movimiento coherente en pacientes con glaucoma y estrabismo. - Reina, Onelia Carballo; Trovajo, Beatriz Barcas (MEDISAN, 2013)
A prospective analytic case-control study was carried out in children with glaucoma or strabismus or both, treated at the Department of Ophthalmology of the Southern Children Hospital in Santiago de Cuba, from January to June 2011, with the purpose of assessing the visual perception of coherent motion in them. The case group included 72 randomly selected patients, and control group with the same number of members who had all their vision. It was determined that children with visual disorders made more errors, omissions and fewer hits, besides being less rapid in solving oriented tests, as they had longer reaction time to do them.